(untitled) (Al-Farooq Journal of Sciences, 2026)
Health institutions in Libya face multiple challenges in the field of applying management information systems, most notably weak technical infrastructure, lack of appropriate training for administrative staff, and weak use of electronic data to support decision-making processes. Based on this problem, this study aimed to measure the level of application of management information systems in health facilities in the Qasr Bin Ghashir area, measure the level of efficiency of administrative decision-making, and test the relationship between the two variables. The study adopted the descriptive analytical approach, and data were collected using a questionnaire distributed to a comprehensive sample of managers and heads of administrative departments consisting of (41) individuals. The results of the study showed that (73.2%) of the sample members had not received any previous training in management information systems. The results also showed that the level of application of management information systems was low (mean = 2.33 out of 5), while the level of efficiency of decision-making was moderate to relatively low (mean = 2.86 out of 5). The results indicated a moderate, positive, and statistically significant correlation between the two variables (correlation coefficient = 0.53). The results also showed that those who had received previous training had a higher level of application (3.04) and higher decision-making efficiency (3.15) compared to those who had not received training. The significance of the study lies in highlighting the training and technical gap in health facilities in the area, and providing practical recommendations to improve the application of management information systems and decision-making efficiency.